The 'like' advocacy facebook environmental campaigns and page followers' behavior in environmental initiatives - Na, Minji (The Philippine Journal of Development Communication, 2013)
By applying agenda-setting theory in social media context, this study examines how environmental campaigns on Social Network Sites (SNSs), specifically Facebook, influence behavior among those "Liked" the environmental pages of EcoWaste Coalition, Greenpeace Philippines, and Tiktok Pilipinas. Results showed that majority of the 76 respondents had been involved in environmental organizations or similar activities before liking the pages. To increase knowledge on environmental concerns was primary reason for liking, while influencing others to join a cause served as a positive reinforcement of their actions. Almost all of the respondents took action after liking the page, including re-posting the posts. Photos posted in the page were found to be an additional factor in influencing followers' environmental behavior. Chi-square with Phi coefficient test showed that prior involvement of similar environment organizations or activities correlated with the level of environmental actions made.